A Heterobimetallic Complex With an Unsupported Uranium(III)−Aluminum(I) Bond: (CpSiMe3)3U−AlCp (Cp = C5Me5) - Minasian, Stefan G; Krinsky, Jamin L; Williams, Valerie A; Arnold, John (Journal of the American Chemical Society, 2008)
A heterobimetallic complex with the first unsupported bond between an actinide and a group 13 element, (CpSiMe3)3U−AlCp* (Cp* = C5Me5) (1), was synthesized by reaction of (CpSiMe3)3U and 1/4(Cp*Al)4 in toluene. Density functional theory calculations indicate that the U−Al bond exhibits some covalent character resulting from a Cp*Al→U charge-transfer.